Copper Deposition Corrosion Elevates Lead Release to Potable Water. Issue 11 (1st November 2015) - Clark, Brandi; Clair, Justin St.; Edwards, Marc
Abstract : Deposition corrosion has been identified as a possible factor contributing to consumer exposure to elevated lead in water after partial lead service line replacement. Dump‐and‐fill tests in two different waters yielded very different results; compared with the control, one water showed a substantial increase (approximately three times) in lead leaching, whereas the other showed little effect when copper was added to water contacting new lead pipes. These differences were consistent with expected trends; lead leaching increased as both the copper solubility in water and the amount of copper deposited on the lead pipe surface increased. Detailed analyses of lead pipes from laboratory studies and field tests in which lead was galvanically connected to copper using various commercial and laboratory connectors were consistent with pure metallic copper deposits on the pipe surface, especially near the galvanic junction with copper. This finding supports a significant deposition corrosion mechanism when copper and lead are galvanically connected.